Features of realization of massage procedure to the persons with the high degree of hypertensive illness - Єфіменко [Pavlo Iefimenko] Павло Богуславович (Slobozhanskyi Herald of Science and Sport, 2013)
In the article the features of application of massage are considered in the physical rehabilitation of persons, patient with hypertensive illness of high degrees. The systems of massage, which are used at this pathology, are considered. The important value of initial position of the massaged man is marked during procedure, specified on the necessity of observance of contra-indications to her realization at ІІ-в and ІІІ degrees of disease. The purpose of work was to find possibility of the use of classic massage at this state of organism. The conducted research showed that the effective variant of procedure is a massage of peripheral parts of body on drainage methods. Necessary initial position of massaged and features of technique and methods of his realization is educed. The analysis of results of inspection of reaction of arteriotony is presented on the drainage massage of shin.